Easy Route to Modified Activated Carbon Honeycombs for Removal of Methyl Mercaptan - Yoon, Hee-Seung; Ryu, SeungKon; Oh, Won-Chun; Zhang, Feng-Jun (Asian Journal of Chemistry, 2011)
In this paper, removal efficiencies of methyl mercaptan on virgin activated carbon honeycomb and surface modified activated carbons honeycombs using NaOH, CuSO4 and MnSO4 solutions were studied. The activated carbons were characterized by nitrogen adsorption, XRD, SEM, TEM and adsorption tests. The treatment of NaOH, CuSO4 and MnSO4 solutions on the activated carbon significantly enhanced the adsorption capacity of methyl mercaptan, despite a notable decrease in microporosity for the case of MnSO4 modified samples. Among the three treatments, copper sulfate modified activated samples have the best results. It is likely that copper sulfate may act as adsorption site for methyl mercaptan.